2020
DOI: 10.1016/j.jmbbm.2020.103711
|View full text |Cite
|
Sign up to set email alerts
|

Extraction force and its determinants for minimally invasive vertical tooth extraction

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
2
13
0
2
Order By: Relevance
“…Furthermore, it was highlighted that this device can be reused several times. The results were consistent with previous findings, which measured vertical tooth extraction forces in real patients, and found that the amount of force required strongly depends on root anatomy and dental status [ 25 , 26 ]. Based on the reports of the dentists, after some minor modifications, our device could be potentially used in real-life conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it was highlighted that this device can be reused several times. The results were consistent with previous findings, which measured vertical tooth extraction forces in real patients, and found that the amount of force required strongly depends on root anatomy and dental status [ 25 , 26 ]. Based on the reports of the dentists, after some minor modifications, our device could be potentially used in real-life conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the clear reduction in force, the dispersion of maximum force of the same root type in the different jaws was relatively high. This is due to the considerably large degree of variability in the physiological and morphological characteristics of PDL, thus corroborating observations in human jaws [ 15 , 32 ].…”
Section: Resultssupporting
confidence: 85%
“…Figure 1 summarizes the entire process, from jaw preparation to the root extraction with a loading machine. Our preliminary analysis revealed that, owing to anatomical properties, such as considerable root divergence and fragility of the examined teeth, splitting the premolars comprises an essential step to reduce the extraction force to a strength comparable to that of humans [ 32 ]. Otherwise, the magnitude of the tooth extraction force in the porcine jaw resulted in premature root or crown fracture.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, pliers should not be used as they require forceful eccentric movements, which distort and damage the alveolar bone. Instead, extraction systems where, for example, a post is screwed into the root and then pulled out of the socket vertically with a lever arm system and without touching the bone are recommended (Figure 20) for atraumatic tooth extraction (Easy X‐Trac System, A.Titan Instruments, Orchard Park) 15 …”
Section: The Predictable Immediate Implant Conceptmentioning
confidence: 99%
“…A silicone index of the prepared tooth serves as guide for atraumatic tooth extraction (Easy X-Trac System, A.Titan Instruments, Orchard Park). 15…”
Section: Atraumatic Extractionmentioning
confidence: 99%